Arboreal concertina locomotion of snake robots on cylinders. (20th December 2017) - Tang, Chaoquan; Shu, Xin; Meng, Deyuan; Zhou, Gongbo
This article proposes a novel gait on cylinders for a snake robot as well as arboreal concertina locomotion gait, including the generation method. The gait on the cylinder of a snake robot is a kind of spatial motion planning that is difficult in manual design. In this article, a planar gait of a snake robot is first constructed, followed by cylindrical gait via a transformation mechanism. In addition, a gait generating scheme of arboreal concertina locomotion gait of snake robots on cylinders is constructed and verified via a simulation platform. Such gait makes advantages on cylindrical motion capability of snake robots and the proposed generation approach for gait construction can be promoted to other cylindrical gaits, reducing design difficulty.